Research Trends on the Use of Artificial Intelligence in Educational Environments in Southeast Asia on Scopus Database: A Bibliometric Analysis (2014-2024) - Zafrullah, Zafrullah; Sembiring, Yanti Kumala; Ramadana, Nurfitri; Gunawan, Resky Nuralisa; Kusumawardhani, Khintan (Innovative: Journal Of Social Science Research, 2024)
This study aims to look at research trends in the Scopus Database regarding the use of AI in educational settings in Southeast Asia. By using keywords that have been determined and selected by the PRISMA method, researchers get 118 documents that are analyzed with the R Program and VOSviewer. From the analysis, it can be concluded that research on AI in Education in Southeast Asia in the Scopus database started from 2014 to 2024, with the peak contribution occurring in the last year. Singapore is the most productive country, followed by Nanyang Technological University (NTU) as the leading affiliate in publications in this field. The most prolific source came from the journal Sustainability (Switzerland), while Sayed Fayaz Ahmad from Pakistan was noted as the author with the most contributions and highest h-index. Paranjape et al. (2019) is the study with the highest citations. There are seven clusters formed, with keywords such as “Computer Aided Instruction”, “Chatbot”, “ChatGPT”, “Assessment”, and “Generative Artificial Intelligence” being recommendations for further research in the field of AI in education in Southeast Asia.